2013 IEEE International Conference on Communications Workshops (ICC) 2013
DOI: 10.1109/iccw.2013.6649303
|View full text |Cite
|
Sign up to set email alerts
|

Towards zero grid electricity networking: Powering BSs with renewable energy sources

Abstract: In this paper we study cellular access networks which solely rely on renewable energy. We consider a cellular network in which a mesh of base stations (BSs) that are powered with renewable sources, and interconnected with wireless backhaul links, cover the service area, and provide connection to few, typically remote, wired network accesses to the national and international backbone. In particular, we study how to dimension BS power generators and energy storage. We start by discussing the BS energy need, that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
72
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(80 citation statements)
references
References 5 publications
0
72
0
Order By: Relevance
“…In [23][24][25], independent hybrid power supply systems, which combine the energy of the sun and wind generated from solar photovoltaic (PV) modules and wind turbines, are presented. Dimensioning PV panels and wind turbines together with their associated energy storage for practical realization of the LTE cellular access networks, which solely rely on renewable energy, is presented in [26]. It is shown that with current PV and wind turbine technology, the size of the renewable energy power system is challenging, but the use of BS sleep modes can provide a significant reduction of the system size.…”
Section: Related Workmentioning
confidence: 99%
“…In [23][24][25], independent hybrid power supply systems, which combine the energy of the sun and wind generated from solar photovoltaic (PV) modules and wind turbines, are presented. Dimensioning PV panels and wind turbines together with their associated energy storage for practical realization of the LTE cellular access networks, which solely rely on renewable energy, is presented in [26]. It is shown that with current PV and wind turbine technology, the size of the renewable energy power system is challenging, but the use of BS sleep modes can provide a significant reduction of the system size.…”
Section: Related Workmentioning
confidence: 99%
“…In [20], [21], energy efficient radio resource management frameworks are proposed for heterogeneous networks that employ multiple radio access technologies. However, the most promising and currently deployed energy-efficient solutions are based on the use of RE to power cellular networks [7]- [9]. The benefit of using RE in cellular networks has been thoroughly investigated in literature [22]- [26].…”
Section: A Related Workmentioning
confidence: 99%
“…In fact, different techniques have been used to achieve energy efficiency such as infrastructure sharing [15], [16], BS ON/OFF switching [17]- [19], radio resource management [20], [21], and energy harvesting from renewable sources to power BSs [7]- [9]. In [15], [16], infrastructure sharing approaches are proposed where multiple cellular operators use the same radio access network infrastructure to reduce the otherwise redundant capacity of BSs that results in energy inefficiency.…”
Section: A Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The result shows that this powering system can reduce the total energy cost with respect to a pure solar system and the traditional connection to the power grid, by 20%-40%. Reference [20] analyzed the feasibility of cellular access networks that exclusively rely on renewable energy sources (e.g., PV panels, wind turbines (in several cases), and energy storage). The results show that integrating renewable energy sources with BS sleep modes can result in significant energy savings, as well as a reduction of the solar system size.…”
Section: Introductionmentioning
confidence: 99%